The complete chloroplast genome sequence of Quercus gilva（Fagaceae） - Zeng, Qin-Meng (Mitochondrial DNA B Resour, 2019)
Quercus gilva is classified as the national second-class protective tree species in China and is widely distributed in Middle East Asia. We determined the complete chloroplast genome sequence for Q. gilva using Illumina sequencing data. The complete chloroplast sequence is 160,763 bp, including large single-copy (LSC) region of 90,292 bp, small single-copy (SSC) region of 18,831 bp, and a pair of invert repeats (IR) regions of 25,820 bp. Plastid genome contains 128 genes, 80 protein-coding genes, 40 tRNA genes, and 8 rRNA genes. Phylogenetic analysis based on 26 chloroplast genomes indicates that Q. gilva is closely related to Q. sichourensis in Fagaceae.